The Impact of Low Flow on Riverine Food Webs in South‐Central Newfoundland. (1st August 2014) - Brush, J. M.; Power, M.; Clarke, K. D.; Pennell, C. J.
Abstract: Low‐flow events can reduce food availability and decrease the feeding niche of consumers within rivers. Stable carbon (δ 13 C) and nitrogen (δ 15 N) isotope and stomach content analyses were employed to evaluate resource use and overlap between fish species in a natural and regulated river in normal and low‐flow years, with the use of multiple methodological approaches providing the best means of understanding short‐term and long‐term observations on fish feeding and resource overlap under changing flow conditions. Diet analyses generally indicated significant inter‐specific differences in the diets of key fish species within rivers and similarities in resource use between rivers. In comparison with fish from the natural river, fish from the regulated river had lower and less inter‐annually variable δ 13 C values. In the natural river, there was a significant reduction and increase, respectively, in δ 13 C and δ 15 N variation in the low‐flow year. Intra‐annual or inter‐annual differences in trophic niche area were not apparent in the regulated river, whereas within the natural river, intra‐annual and inter‐annual differences in trophic niche were found. Resource overlap between key fish species was also higher in the low‐flow year and lower in the spring and higher in the summer as a result of differences in flow. Resource overlap was also higher between rivers in the low‐flow year. High resource overlap between rivers during decreased summer flow indicates a strong effect of flow on river organisms, where both fish and their invertebrate prey resources are concerned. Copyright © 2014 John Wiley & Sons, Ltd.